Pemanfaatan TikTok sebagai Media Literasi Digital: Analisis Konten Video Kesehatan Mental - Mufti Lanang Adi Satya; Citra Zirda Lena; Allia Desti Azizah; Clarita Angeli (CV. ITTC INDONESIA, 2025)
TikTok has become one of the most influential platforms for disseminating mental health information through emotionally driven and visually engaging short videos. This study examines how mental health is represented in TikTok content, particularly narratives that link psychological stress to physical conditions, and how such representations relate to users’ digital health literacy. Using a qualitative approach and a library research design, data were collected from scholarly publications and analyzed through content analysis. Findings from the reviewed literature show that mental health narratives on TikTok commonly employ dramatic storytelling, classical references, and legitimacy strategies such as rationalization, authorization, and moralization to enhance message credibility. However, these strategies may also lead to oversimplification, misinformation, and self-diagnosis among users with limited digital literacy. The study highlights that digital literacy plays a central role in enabling users, especially adolescents and university students to critically evaluate online health information. Strengthening digital literacy is therefore essential to reducing misinformation, preventing misinterpretation, and supporting the constructive use of social media as an educational medium for mental health awareness.